Characterization of municipal solid waste in the municipality of Simão Dias (SE) - Almeida, Camila Couto de; Ventura, Katia Sakihama (Periódico Eletrônico Fórum Ambiental da Alta Paulista, 2022)
Inadequate disposal of municipal solid waste (MSW) is a common practice in some Brazilian municipalities, raising the level of economic and socio-environmental impacts. The main objective was to characterize the MSW of the municipality of Simão Dias (SE) through field visitations. The elaboration tools were a checklist, characterization sheet, and observation evaluation matrices (GUT and SWOT). Eighty-four (84) points were identified as irregular deposit spots for these materials, of which the volume estimated was around 6,150m³. A disposal period of 3 years has been considered in the visited places, and the estimated cost was approximately R319,234 (R2.63/hab. year) for the withdrawal of MSW at all points. Most observations (73.8%) occurred due to the accumulation of construction waste. The main challenges were the inexistence of public policies for proper MSW management, as recommended by Federal Law 12.305/2010; lack of knowledge about the origin and quantification of MSW by the local government; lack of adequate segregation at the generating source and inefficiency of actions for selective collection. Among the opportunities that stand out, the performance of the existing cooperative and the participation in an inter-municipal consortium are the most noteworthy. The main contribution of the study was the organization of information to support municipal decision-making in this sector.